ANALYSIS OF THE EFFECTIVENESS OF THE ARMED FORCES COMMAND OPERATIONS IN SECURING THE RI-SINGAPORE BORDER TO PREVENT CRIMINAL ACTS AT SEA IN ORDER TO CREATE MARINE SECURITY - Adha, Fajar; Syamsul, Heru; Agus H, Prasetyo (AGUSPATI Research Institute, 2025)
This study examines the effectiveness of Fleet Command operations in securing the Indonesia–Singapore maritime border to prevent criminal activities at sea. The Malacca and Singapore Straits, as vital international shipping lanes, are highly vulnerable to security threats such as piracy, smuggling, and territorial violations. As the main naval force, the Indonesian Navy is responsible for maintaining maritime security through border security operations and coordinated patrols with the Royal Singapore Navy. Using a qualitative approach, data were collected through in-depth interviews, literature review and analyzed with NVIVO 12 Pro. Informants included operational officers from, Guspurla and Guskamla. The results indicate that operational effectiveness is determined by three key factors: timely and accurate intelligence dissemination, strong inter-agency and regional cooperation, and optimized deployment of naval assets. The findings suggest that while has performed its duties effectively, improvements are needed in surveillance technology, patrol duration and coordination mechanisms. This research contributes to strengthening maritime security strategies in Indonesia–Singapore border areas, supporting regional stability and international confidence in Indonesia’s maritime capabilities.